The larger grain borer: more trouble in store - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The larger grain borer, a beetle pest introduced accidentally into Africa, is relentlesly spreading through maize growing areas where, if unchecked, it can decimate stocks of stored maize and dried cassava. Until 1981 the larger grain borer (LGB),...